Privacy Policy on Smart Contracts in E-Commerce Transactions - Mariska Zena Wilona; Emmy Latifah; Hari Purwadi (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2021)
The technology of smart contract is a new technology applied in online trading. This technology has the possibility of errors and its arrangement that results in losses to buyers. This study was aimed to examine the legal certainty for the users smart contract in e-commerce transactions in Indonesia. The method used was the normative juridical method. The results of the study indicate that the privacy policy on smart contracts in e-commerce transactions based on national and international laws still has a legal vacuum in which the aspect of national law is guided by the ITE Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 and the Regulation of the Minister of Communication and Information Number 20 of 2016 concerning Personal Data Protection in Electronic Systems. Then, in the aspect of international law referring to the UNCITRAL Model Law on Electronic Commerce (MLEC), it also establishes the rules for the formation and validity of contracts made electronically and for attribution.